SECULAR VARIATION IN THE MAJOR-ION CHEMISTRY OF SEAWATER: EVIDENCE FROM FLUID INCLUSIONS IN CRETACEOUS HALITES - Timofeeff M.N.; Lowenstein T.K.; da Silva M.A.M.; Harris N.B. (My University, 2006)
The major-ion (Mg2+, Ca2+, Na+, K+, multiscripts(SO, 4, mml:none(), mml:none(), 2 -), and Cl-) chemistry of Cretaceous seawater was determined from analyses of seawater-derived brines preserved as fluid inclusions in marine halites. Fluid inclusions in primary halite from three evaporite deposits were analyzed by the environmental scanning electron microscopy (ESEM) X-ray energy dispersive spectrometry (EDS) technique: the Early Cretaceous (Aptian, 121.0-112.2 Ma) of the Sergipe basin, Brazil and the Congo basin, Republic of the Congo, and the Early to Late Cretaceous (Albian to Cenomanian, 112.2-93.5 Ma) of the Khorat Plateau, Laos, and Thailand. The fluid inclusions in halite indicate that Cretaceous seawater was enriched several fold in Ca2+, depleted in multiscripts(SO, 4, mml:none(), mml:none(), 2 -), Na+, and Mg2+, and had lower Na+Cl-, Mg2+/Ca2+, and Mg2+/K+ ratios compared to modern seawater. Elevated Ca2+ concentrations, with Ca2+ > multiscripts(SO, 4, mml:none(), mml:none(), 2 -) at the point of gypsum saturation, allowed Cretaceous seawater to evolve into Mg2+-Ca2+-Na+-K+-Cl- brines lacking measurable multiscripts(SO, 4, mml:none(), mml:none(), 2 -).The major-ion composition of Cretaceous seawater was modeled from fluid inclusion chemistries for the Aptian and the Albian-Cenomanian. Aptian seawater was extreme in its Ca2+ enrichment, more than three times higher than present day seawater, with a Mg2+Ca2+ ratio of 1.1-1.3. Younger, Albian-Cenomanian seawater had lower Ca2+ concentrations, and a higher Mg2+Ca2+ ratio of 1.2-1.7. Cretaceous (Aptian) seawater has the lowest Mg2+Ca2+ ratios so far documented in Phanerozoic seawater from fluid inclusions in halite, and within the range chemically favorable for precipitation of low-Mg calcite ooids and cements. Results from halite fluid inclusions, together with Mg2+Ca2+ ratios measured from echinoderm and rudist calcite, all indicate that Early Cretaceous seawater (Hauterivian, Barremian, Aptian, and Albian) had lower Mg2+Ca2+ ratios than Late Cretaceous seawater (Coniacian, Santonian, and Campanian). Low Aptian-Albian Mg2+Ca2+ seawater ratios coincide with negative excursions of 87Sr86Sr ratios and δ34SSO4, and peak Cretaceous ocean crust production rates, all of which suggests a link between seawater chemistry and midocean ridge hydrothermal brine flux. © 2006 Elsevier Inc. All rights reserved.
Keywords: Мезозой::Меловая::Верхний::Коньякский; Мезозой::Меловая::Верхний::Сантонский; Мезозой::Меловая::Верхний::Кампанский; Мезозой::Меловая::Верхний::Сеноманский; Мезозой::Меловая::Нижний::Альбский; Мезозой::Меловая::Нижний::Аптский; Мезозой::Меловая::Нижний::Барремский; Мезозой::Меловая::Нижний::Готеривский; Mesozoic::Cretaceous::Upper::Campanian; Mesozoic::Cretaceous::Upper::Santonian; Mesozoic::Cretaceous::Upper::Coniacian; Mesozoic::Cretaceous::Upper::Cenomanian; Mesozoic::Cretaceous::Lower::Albian; Mesozoic::Cretaceous::Lower::Aptian; Mesozoic::Cretaceous::Lower::Barremian; Mesozoic::Cretaceous::Lower::Hauterivian